Pengembangan Buku Pintar Berbasis Android Pada Materi Jamur Bernilai Ekonomis Untuk Siswa Kelas X SMK: Android-Based Smart Book Development of Economical Value of Mushroom Material for Class X Vocational High School - Fira Idayesti; Revis Asra; Upik Yelianti (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2022)
The 21st century technology and communication advancement require teachers to use learning media in Android-based smart books. This study aims to develop android-based biology learning media on mushroom material and test the feasibility of learning media developed according to media experts and material experts. The development employs used the ADDIE model by Lee & Owen, which consists of Analysis, Design, Development, Implementation, and evaluation stages. The product was tested by students of class X SMK-SPP Negeri 3 Kerinci and assessed by media experts and content experts. Their responses were collected through a questionnaire. The results of this study are learning media in the form of an Android-based mushroom smart book made in the Android Package (.apk) format using Adobe Flash Professional CS6 software. The product is attractive, practical, and easily accessible. The product is suitable used in learning based on the media expert's assessment of 94% and the material expert's assessment of 96.3% (very feasible category)